Pengaruh Umur, Pendidikan dan Jumlah Tanggungan Keluarga Terhadap Pendapatan Pekerja Perempuan Sektor Informal di Kota Denpasar - Dewi, Made Ayu Laksmitha; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Informal sector is a sector that has a strategic role in national economic development. This study aimed to determine effect of simultaneous and partial age, education and dependents against income of female workers in informal sector in Denpasar City. The data used in this study is primary data by distributing questionnaires. The samples used as 90 female workers using sample determination method that is Random Sampling. The analysis technique used in this research is multiple linear regression analysis. The result show that of age, education and number of dependents have a significant effect simultaneously to the income of female workers in informal sector in Denpasar City. The partial education and the number of dependents have positive and significant effect on the income of female workers in informal sector in Denpasar. Partially age have negative and significant effect on earnings of female workers in informal sector in Denpasar City.